1990
DOI: 10.1038/346191a0
|View full text |Cite
|
Sign up to set email alerts
|

The c-ets proto-oncogenes encode transcription factors that cooperate with c-Fos and c-Jun for transcriptional activation

Abstract: Cell transformation by oncogenes leads to changes in gene expression. A key event in this process seems to be activation of the transcription factors AP-1 and PEA 3. Their synergistic activities are required for efficient activation of transcription from different promoters by many different oncogenes, serum growth factors and the tumour promoter TPA. We show here that the products of the ets-1 and -2 proto-oncogenes, whose biological function was previously unknown, are transcription factors that activate tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
289
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(299 citation statements)
references
References 18 publications
10
289
0
Order By: Relevance
“…Binding to E74ml, a mutant E74 oligonucleotide, was virtually undetectable (lane 2). E74ml contains a GGAA?AGAA substitution in the core of the ETS recognition site, which we and others have previously shown to obliterate the binding of ETS factors (Wasylyk et al, 1990;Nye et al, 1992;Thomas et al, 1995Thomas et al, , 1997. ELF3 also binds to a weaker ETS-binding site from the GM-CSF promoter (GM ± lane 4), but not to an AGAA mutant of this oligonucleotide (GMml ± lane 5).…”
Section: Elf3 Displays Sequence Speci®c Binding To Oligonucleotides Cmentioning
confidence: 84%
“…Binding to E74ml, a mutant E74 oligonucleotide, was virtually undetectable (lane 2). E74ml contains a GGAA?AGAA substitution in the core of the ETS recognition site, which we and others have previously shown to obliterate the binding of ETS factors (Wasylyk et al, 1990;Nye et al, 1992;Thomas et al, 1995Thomas et al, , 1997. ELF3 also binds to a weaker ETS-binding site from the GM-CSF promoter (GM ± lane 4), but not to an AGAA mutant of this oligonucleotide (GMml ± lane 5).…”
Section: Elf3 Displays Sequence Speci®c Binding To Oligonucleotides Cmentioning
confidence: 84%
“…However, PU.1-transfected HT1080 cells expressed similar levels of N-ras mRNA to the parental cells and mock transfectants ( Figure 3A and B). As a member of the Ets family proteins is one of the nuclear targets of the ras signalling pathway to activate rasresponsive elements (Wasylyk et al, 1990;Galang et al, 1994), the ectopic expression of PU. I may perturb endogenous Ets family proteins, which mediate the ras signals crucial for maintenance of the transformed phenotypes of HT1080 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] The ets family of transcription factors has a DNA-binding domain in common that binds to a core GGA(A/T) DNA sequence. 21,22 In situ hybridization studies have shown that the proto-oncogene c-ets is expressed in endothelial cells at the beginning of blood vessel formation, under normal and pathological conditions. 23,24 Thus, previous reports suggest that the ets family may activate the transcription of genes encoding collagenase 1, stromelysine 1 and urokinase plasminogen activator, which are proteases involved in extracellular matrix degradation.…”
Section: Figure 3 Effect Of the Transfection Of Hgf Vector On The Vasmentioning
confidence: 99%